ANALISIS KESEHATAN LINGKUNGAN DALAM PENGELOLAAN SAMPAH RUMAH TANGGA DI KELURAHAN KENALI BESAR KOTA JAMBI TAHUN 2025 - Andini - (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2026)
Household waste management in urban areas remains an important issue because it affects public health and environmental quality. In Jambi Province, waste management coverage has only reached 53.81% of the 70% target, indicating that current practices are still not optimal. This condition may increase the risk of environment-related diseases and lower sanitation quality. Kenali Besar Subdistrict in Jambi City is one of the areas with high waste generation and inadequate waste management. This study aimed to examine the relationship between knowledge, attitudes, age, education level, income, and waste bin ownership with household waste management. A quantitative cross-sectional design was used involving 70 housewives selected through multistage random sampling. Data were collected using a validated Environmental Health Risk Assessment (EHRA)-based questionnaire and an observation checklist, then analyzed using Chi-Square tests. The results showed that 50% of respondents had poor household waste management practices, while 50% had good knowledge. Attitudes (p=0.017), education level (p=0.001), income (p=0.002), and waste bin ownership (p=0.000) were significantly associated with waste management. Meanwhile, knowledge (p=0.198) and age (p=0.473) were not significantly associated. In conclusion, improving community attitudes and access to waste management facilities is essential to enhance household waste management practices.